Quasi-guided modes resulting from the band folding effect in a photonic crystal slab for enhanced interactions of matters with free-space radiations - Sun, Kaili; Cai, Yangjian; Levy, Uriel; Han, Zhanghua (Beilstein Journal of Nanotechnology, 2023)
We elucidate that guided modes supported by a regular photonic crystal slab structure composed of a square lattice of air holes in a silicon slab will transition into quasi-guided (leaky) modes when the radius of every second column of air holes is changed slightly. This intentional geometric perturbation will lead to a doubling of the period in one direction and the corresponding shrinkage of the first Brillouin zone. Because of the translational symmetry in the k-space, leaky waves inheriting the spatial dispersion of the original guided modes, which do not interact with external radiation, will appear with the dispersion curves above the light cone. Our results show that ultrahigh Q-factor resonances with large operating bandwidth can be achieved. Interestingly, the perturbation in only one direction of the photonic lattice will lead to an in-plane wave number-dependent resonance characteristic in both directions. Our numerical results demonstrate a local enhancement of the electric field magnitude by the order of 102, which is even more significant than those in most plasmonic structures. These quasi-guided modes with superior properties will provide a new platform for efficient light–matter interactions.
Keywords: guided modes; light–matter interactions; photonic crystal slab